The Relationship Of Breast Examination Examination Using Video Media With Adolescent's Knowledge About Breading In Simpang Four Village,Sei Rampah District In 2020 - rosmani sinaga (Institute of Computer Science (IOCS), 2021)
Cancer is one of the non-communicable diseases that is a burden on health throughout the world. Cancer is a disease characterized by abnormal cells that can grow uncontrollably and have the ability to invade and move between cells and body tissues. The World Health Organization/World Health Organization mentions cancer as one of the main causes of death worldwide (Ministry of Health, 2019). Breast cancer early detection activities can use the Clinical Breast Examination (SADANIS) or Clinical Breast Examination (CBE) method and by teaching Breast Self- Examination (BSE). SADANIS and BSE aim to find lumps in the breast as early as possible so that early action can be taken (Kemenkes, 2015). The purpose of this study was to identify the relationship between Breast Self-Examination Extension Using Video Media and Adolescent Knowledge About Consciousness in Simpang Empat Village, Sei Rampah Subdistrict in 2020. The type of research used was a quasi-experimental type of research using a one group pretest posttest design with the man witney test. U. The sample size in this study was 49 respondents who met the inclusion and exclusion criteria. Based on the results of research analysis in the group before and after the intervention, the average value of the knowledge of the respondents before receiving counseling was 63.81, while the average value after receiving counseling was 35.19. After the statistical test was carried out, the Mann Witney U test results obtained p value = 0.000 (p <0.05) meaning that there was an effect of breast self-examination (BSE) counseling using video on respondents' knowledge.